Personalizing the BioPsychoSocial Approach: “Add-Ons” and “Add-Ins” in Generalist Practice - Ventres, William B.; Frankel, Richard M. (Frontiers in Psychiatry, 2021)
Generalist practitioners often find interacting with patients deeply satisfying and joyful; they also experience encounters that are challenging and complex. In both cases, they must be aware of the many issues that affect the processes and outcomes of patient care. Although using the BioPsychoSocial approach is an important, time-tested framework for cultivating one’s awareness of patients’ presenting concerns, recent developments suggest that additional frames of reference may enhance communication and relationships with patients. In this article, we describe several additions to the BioPsychoSocial approach, considerations we call “add-ons” and “add-ins”. We invite generalists and, indeed, all health care practitioners, to consider how they can improve their ongoing care of patients by personalizing these and other additions in their day-to-day work with patients.